2005
DOI: 10.1159/000088052
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Cancer Gene Therapy and Its Application in Esophageal Carcinoma

Abstract: Advances in molecular genetics have accelerated the understanding of the genetic basis of many diseases. This is particularly true for esophageal adenocarcinoma with its well-defined premalignant lesions. At the same time, remarkable progress in recombinant DNA technology has enabled the development of molecular treatments for inherited disorders, infectious diseases and cancer. In recent years, especially the development of gene therapy systems as new treatment or prevention strategies for various malignant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…5 This study investigated and compared the in vitro and in vivo effectiveness of HSV-tk/GCV suicide gene therapy in gastroesophageal junction and gastric body adenocarcinomas. Very few gene therapy studies have been reported for junctional or esophageal adenocarcinoma, with esophageal cancer studies focusing on squamous cell carcinoma [6][7][8][9] and gastric cancer studies focusing on the non-junctional/ non-cardia gastric cancers. 8 The limited number of esophageal adenocarcinoma gene therapy studies have unfortunately mostly used inappropriate cell lines or animal models, reflecting the paucity of suitable models.…”
mentioning
confidence: 99%
“…5 This study investigated and compared the in vitro and in vivo effectiveness of HSV-tk/GCV suicide gene therapy in gastroesophageal junction and gastric body adenocarcinomas. Very few gene therapy studies have been reported for junctional or esophageal adenocarcinoma, with esophageal cancer studies focusing on squamous cell carcinoma [6][7][8][9] and gastric cancer studies focusing on the non-junctional/ non-cardia gastric cancers. 8 The limited number of esophageal adenocarcinoma gene therapy studies have unfortunately mostly used inappropriate cell lines or animal models, reflecting the paucity of suitable models.…”
mentioning
confidence: 99%